The potato ladybird beetle Henosepilachna vigintioctomaculata (Motsch.): classification, morphology and harmfulness (review) - M. V. Ermak; N. V. Matsishina (Овощи России, 2022)
The 28-spotted potato ladybird beetle belongs to the subfamily Epilachninae, which is comprised exclusively by phytophagous insects. The potato ladybird beetle is a dangerous pest of potato in the south of the Russian Far East. Besides potato, it causes damage to tomatoes, cucumbers, watermelons, marrows and eggplants. Adult beetles and larvae eat the parenchyma of leaves severely damaging them. As the result, leaves turn yellow and wither. One beetle can eat up to 15 cm2 of leave surface on average per day, and 300-700 cm2 over its lifetime. A larva can eat from 20 to 30 cm2 of leave surface while developing. This significantly reduces the yield. The body of an adult beetle is small (males, 4-6 mm; female, 5-7 mm), dome-shaped, and elliptical. The elytra are yellow or brownish with 28 black round spots. Some spots, especially the ones along the line of junction, can partially merge. The color of the underside of male beetles is lighter than in females. Male beetles have yellow or less frequently darkened prothorax, mesothorax and metathorax, epimera, and the uppermost edge of the sternites of the abdomen. The anal sternite of the abdomen has a curve with two depressions. The underside of a female beetle is black. The uppermost edge of the anal sternite is straight and with a flat depression. The body of a larva is greyish, oval and with numerous setae. There are 4 rows of black chitinous spinules on the back. Depending on an instar, larvae have a different number of projections on the chitinous spinules. Pupae are exarate, light yellow, and have larval skin remnants at the apex of the abdomen. There are two large black spots on the backside of the thoracic segments. The spots on the abdominal segments are smaller. Fairly long protruding setae grow sparsely on the bodies of pupae. Eggs of the potato ladybird beetle are yellow, elongated, with a pointed apex and a flat bottom. The surface of an egg is characterized by a fine cellular structure.